Reduced risk of recurrent pneumothorax for sirolimus therapy after surgical pleural covering of entire lung in lymphangioleiomyomatosis - Teiko Sakurai (BMC, 2021)
Abstract Background Patients with lymphangioleiomyomatosis (LAM) frequently experience pneumothorax. Although sirolimus is the standard therapy for LAM, its effect on pneumothorax is controversial. Recently, total pleural covering (TPC) and modified TPC (mTPC) were introduced as surgical treatment options for pneumothorax for patients with LAM. However, the effect of sirolimus on the recurrence of pneumothorax in patients who underwent the treatments is still uncertain. We hypothesized that some clinical factors including sirolimus treatment could predict postoperative recurrence of pneumothorax. In order to clarify this hypothesis, we retrospectively analyzed the clinical data from 18 consecutive patients with LAM who underwent 24 surgical pleural covering of entire lung (SPC) as 17 TPC and 7 mTPC against pneumothoraces from surgical database between January 2005 and January 2019, and we determined the predictors of postoperative recurrence. Results Of the 24 surgeries of SPC, 14 surgeries (58.3%) had a history of two or more ipsilateral pneumothoraces, and 11 surgeries (45.8%) had a history of ipsilateral pleural procedures before SPC. Sixteen surgeries (66.6%) in 12 patients received treatment of sirolimus after SPC (sirolimus group). With a median follow-up time of 69.0 months after SPC, four surgeries (16.6%) in three patients had a postoperative recurrence, and the 5-year recurrence-free survival (RFS) after SPC was 82.9%. In patients with postoperative recurrence, serum level of vascular endothelial growth factors D was significantly higher than that in those with non-recurrence (3260.5 vs. 892.7 pg/mL, p = 0.02), and the rate of sirolimus treatment in the recurrence group was significantly lower than that in the no-recurrence group (0 vs. 80%, p = 0.006). The log-rank test showed that the RFS of the sirolimus group (sirolimus use after SPC) was significantly better than that of the non-sirolimus group (p = 0.001), and no significant difference was observed for other factors. Conclusion We first reported sirolimus might effectively suppress the recurrence of pneumothoraces in LAM patients who received SPC. Sirolimus induction after SPC (TPC or mTPC) might be a feasible option for frequent pneumothorax in LAM.